4(3x+5)=14-12x-46

Simple and best practice solution for 4(3x+5)=14-12x-46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x+5)=14-12x-46 equation:



4(3x+5)=14-12x-46
We move all terms to the left:
4(3x+5)-(14-12x-46)=0
We add all the numbers together, and all the variables
4(3x+5)-(-12x-32)=0
We multiply parentheses
12x-(-12x-32)+20=0
We get rid of parentheses
12x+12x+32+20=0
We add all the numbers together, and all the variables
24x+52=0
We move all terms containing x to the left, all other terms to the right
24x=-52
x=-52/24
x=-2+1/6

See similar equations:

| x-9/4=2/4 | | 3x+42/7+x+33/5=17 | | 14y+6+y=5y-34 | | x+6-5x=23-8x | | 45=6(7n+9) | | 36+12y=19-42+13y | | -7a^2-4+8a=8a-8a^2 | | 3x24=39x | | 15-3m=4.19 | | .25x+19=69 | | 2h/7-2=111/14 | | 1/5y-2=-18 | | 8+8(1+6x=352 | | -3(2s-2)-6=-3(5s+6)-3 | | 7x-10+2x=79x-16 | | 21-(x+9)=4x-3 | | F(x)=√×+12/4 | | 1-x+4x=9+5x | | 18x+2x=160 | | 16=4x+60 | | 36+5b=6(b+4)+5 | | -2(3x-1)=4x-18 | | 6(2x+8)-2=2(x-2) | | 692x+8)-2=2(x-2) | | -15x+4-4(x-1)=-4x-(14x-3)+4 | | -(4-7x)=23-2x | | 3=45.7,12=x | | s-1.9*15=4.6 | | 3=45.7,6=x | | 3=45.7,6+x | | s-1.6*15=4.6 | | X=48x+37 |

Equations solver categories